Menertawakan “Apokalipsis” dalam Film "This is the End" dan Relevansinya untuk Pendidikan Agama - Prajna Putra Mahardika, Amadea (Vocat : Jurnal Pendidikan Katolik, 2024)
This article examines the use of apocalyptic themes in the film *This is the End* and its impact on public understanding of the end times, with a focus on its relevance to Christian religious education. The film presents the apocalyptic theme through humor, offering an alternative approach that reduces the fear associated with the concept of doomsday. The methodology used film analysis and literature review to examine apocalyptic representations in popular culture and to compare them with the Christian eschatological concept that emphasizes hope and restoration. The study concluded that Christian religious education could leverage this approach to dismantle fear-based narratives in popular culture and foster a positive eschatological understanding. Thus, this approach contributes to the formation of critical attitudes and ethical reflection regarding individual roles and responsibilities in the world.